PERANCANGAN ILUSTRASI NOVEL “AKU ANAK BROKEN HOME” KARYA DENNIS CHRISTOPHER - Rinaldi, Rana Syakirah; Ruslan, Arief (Kartala, 2023)
Reading a novel book isn’t that hard, because it’s light reading and neat reading flow make it’s easy to understand. This paper explain how an illustration could be a media support for a novel book. According to interview with a novelist, Dennis Christopher himself that he needs an illustration as a story reinforcement for a novel he wrote named “ I’m A Broken Home Kids”. This novel book is about how it feels to be a broken home kids, in this novel book Dennis want something different from his previous books, he wanted to add an illustration for each story in this book. According to Dennis himself visualization is very important, adding an illustration in each page can touch audience emotions and also strengthen the content of the story. therefore the creator finally made an illustration for each sheet of Dennis’s novel book named “ I’m A Broken Home Kids”.